WORKSHEET BASED ON SOCIOSCIENTIFIC ISSUES TO IMPROVE ANALYTICAL SKILL - Ulvy Shellyana Arifin; Hanin Niswatul Fauziyah (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
The research was intended to develop the worksheet  based on socioscientific issues that test expedibility, practical and effective in development the ability to think analytically of learners. The research site was conducted at SMPN 4 Ponorogo. The research method used research and development, with implementing research model of brog and gall. The research tools used were expert validation analysis sheets, assessments response and so on are used to test analytical thinking. And then the data treated was analyzed quantitatively as well as descriptive. Research results suggested that the product was worthy of using in the learning process. The product was also practical and effective in using to improve the ability of student analytical thought